ANALISA KINERJA BANK SYARIAH DAN BANK KONVENSIONAL PASCA KRISIS KEUANGAN GLOBAL : PERSPEKTIF BASEL III (STUDI PADA BANK SYARIAH INDONESIA DAN BANK MANDIRI) - Mirna Desriani; Li’ilzam Nuur; M. Adrian Rizaldi; Mayangsari Mayangsari; Yusrizal Yusrizal (Journal of Innovative and Creativity, 2026)
The global financial crisis prompted the strengthening of international regulatory frameworks through the implementation of Basel III, which emphasizes capital adequacy, liquidity stability, and leverage control to mitigate systemic risks. This study aims to compare the performance of Bank Mandiri and Bank Syariah Indonesia (BSI) for the 2022-2024 period using a quantitative descriptive approach to dissect the characteristics of both banking models in complying with post-crisis standards. The analysis reveals that Bank Mandiri represents an aggressive-dynamic ‘Capital Efficiency & Liquidity Sweat’ strategy, where leverage optimization and the minimization of idle liquid assets (LCR 103.52%) are tactically utilized to drive intermediation efficiency and profitability. Conversely, BSI demonstrates 'Ethical Finance Resilience' by maintaining a conservative liquidity posture and robust capital quality based on stable real-asset financing. The study concludes that while Bank Mandiri successfully transforms Basel III regulations into an agile growth engine, BSI proves that stringent risk management without complex derivative instruments fosters solid systemic stability for national banking resilience.